Comparison of liver cancer incidence and survival by subtypes across seven high‐income countries. Issue 12 (14th September 2021) - Rutherford, Mark J.; Arnold, Melina; Bardot, Aude; Ferlay, Jacques; De, Prithwish; Tervonen, Hannah; Little, Alana; Bucher, Oliver; St Jacques, Nathalie; Gavin, Anna; Engholm, Gerda; Møller, Bjørn; et al.
Abstract: International comparison of liver cancer survival has been hampered due to varying standards and degrees for morphological verification and differences in coding practices. This article aims to compare liver cancer survival across the International Cancer Benchmarking Partnership's (ICBP) jurisdictions whilst trying to ensure that the estimates are comparable through a range of sensitivity analyses. Liver cancer incidence data from 21 jurisdictions in 7 countries (Australia, Canada, Denmark, Ireland, New Zealand, Norway and the United Kingdom) were obtained from population‐based registries for 1995‐2014. Cases were categorised based on histological classification, age‐groups, basis of diagnosis and calendar period. Age‐standardised incidence rate (ASR) per 100 000 and net survival at 1 and 3 years after diagnosis were estimated. Liver cancer incidence rates increased over time across all ICBP jurisdictions, particularly for hepatocellular carcinoma (HCC) with the largest relative increase in the United Kingdom, increasing from 1.3 to 4.4 per 100 000 person‐years between 1995 and 2014. Australia had the highest age‐standardised 1‐year and 3‐year net survival for all liver cancers combined (48.7% and 28.1%, respectively) in the most recent calendar period, which was still true for morphologically verified tumours when making restrictions to ensure consistent coding and classification. Survival from liver cancers is poor in all countries. The incidence of HCC is increasing alongside the proportion of nonmicroscopically verified cases over time. Survival estimates for all liver tumours combined should be interpreted in this context. Care is needed to ensure that international comparisons are performed on appropriately comparable patients, with careful consideration of coding practice variations. Abstract : What's new? International comparisons of liver‐cancer survival have been hampered by variations in coding and registration practices. In this study, the authors compared incidence and survival trends in seven countries. They found that incidence rates have increased over time across all jurisdictions, particularly for hepatocellular carcinoma (HCC), with the largest relative increase in the UK. They also found that Australia had the highest net survival rates. The authors emphasize that establishing fair and comparable international benchmarks in liver‐cancer survival, incidence, and mortality is key to understanding and addressing disparities.